2017
DOI: 10.1093/molbev/msx075
|View full text |Cite
|
Sign up to set email alerts
|

Single Cell Transcriptomics, Mega-Phylogeny, and the Genetic Basis of Morphological Innovations in Rhizaria

Abstract: The innovation of the eukaryote cytoskeleton enabled phagocytosis, intracellular transport, and cytokinesis, and is largely responsible for the diversity of morphologies among eukaryotes. Still, the relationship between phenotypic innovations in the cytoskeleton and their underlying genotype is poorly understood. To explore the genetic mechanism of morphological evolution of the eukaryotic cytoskeleton, we provide the first single cell transcriptomes from uncultured, free-living unicellular eukaryotes: the pol… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
36
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
2
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(41 citation statements)
references
References 79 publications
5
36
0
Order By: Relevance
“…Recent phylogenomic analyses focusing on Rhizaria show a basal split between two major assemblages, Cercozoa (=Filosa) on the one side, and Endomyxa plus Retaria on the other side (e.g. Sierra et al 2016;Krabberød et al 2017). In this context, the phylogenetic position of the clade comprising Aquavolonida, Tremulida, and NC12 (if they are confirmed to form a clade) becomes of particular significance.…”
Section: Paradinium Poucheti Eu189029mentioning
confidence: 99%
See 1 more Smart Citation
“…Recent phylogenomic analyses focusing on Rhizaria show a basal split between two major assemblages, Cercozoa (=Filosa) on the one side, and Endomyxa plus Retaria on the other side (e.g. Sierra et al 2016;Krabberød et al 2017). In this context, the phylogenetic position of the clade comprising Aquavolonida, Tremulida, and NC12 (if they are confirmed to form a clade) becomes of particular significance.…”
Section: Paradinium Poucheti Eu189029mentioning
confidence: 99%
“…Their exact phylogenetic position within Rhizaria remains unresolved, but they typically appear distinct from both core Cercozoa (previously Filosa) and Endomyxa (Bass et al 2009a;Howe et al 2011). On the basis of recent phylogenomic analyses placing the root of the rhizarian radiation between Cercozoa (Filosa) and Endomyxa + Retaria (Sierra et al 2016;Krabberød et al 2017), this group may therefore form one of the deepest branching rhizarian lineages. NC11 was shown by Howe et al (2011) to contain Tremula longifila, a biflagellate gliding cell (ATCC 50530), which along with its direct relatives inhabits freshwater sediments and soil.…”
mentioning
confidence: 99%
“…I compared the classifications against >200 phylogenetic studies from class to kingdom levels, giving priority to studies with larger ingroup, greater number of genes and most recent treatments (for minor deep diverging groups). In brief, the following studies were used to extract much of the class to domain level classification information: Yoon et al (2006), Ruhfel et al (2014), Magallon et al (2015), Leliaert et al (2017) (Archaeplastida); Fiore-Donno et al (2010), Lahr et al (2013), Cavalier-Smith et al (2015b, 2016), Tekle et al (2016), Kang et al (2017), Tekle & Wood 2017 (Amoebozoa); Kolisko 2011, Kamikawa et al (2014), Radek et al (2014), Cavalier-Smith (2016), Yubuki et al (2017) (Excavata); Grant et al (2009), Riisberg et al (2009), Brown & Sorhannus (2010), Yang et al (2012), Cavalier-Smith & Scoble (2013), Shiratori et al (2015, 2017), Yubuki et al (2015), Aleoshin et al (2016), Derelle et al (2016), Dumack (2016), Gao et al (2016), Krabberød et al 2017, Reñé et al (2017) (Harosa); Brown et al (2009, 2013), Cavalier-Smith & Chao (2010), Zhang (2011), Glücksman et al (2013), Nosenko et al 2013, Paps et al (2013), Yabuki et al (2013), Telford et al 2015; Torruella et al (2015), Whelan et al (2015), Corsaro et al (2016), Carr et al (2017), Dohrmann & Wöhrheide (2017), Hehenberger et al (2017), Schiffer et al (2017), Simion et al (2017), Tedersoo et al (2018), (Opisthokonta); Yoon et al (2008, 2011), Wegener Parfrey et al (2010, 2011), Burki et al (2012, 2016), Cavalier-Smith & Chao (2012), Yabuki et al (2012, 2014) Cavalier-Smith et al (2014, 2015a), Burki (2014), Katz & Grant (2014), Sharpe et al (2015), Brown et al (2017) (minor groups and all eukaryotes). Following the divergence time estimates of Wegener Parfrey et al (2011),...…”
Section: Methodsmentioning
confidence: 99%
“…Few species have been described, and these are all parasitic, infecting a wide array of hosts, such as dinoflagellates, copepods, ciliates, crabs and fish (Harada et al 2007, Skovgaard & Daugbjerg 2008, Skovgaard et al 2009). Recent work using multiple displacement amplification on isolated single cells of radiolarians has revealed a surprisingly large MALV diversity and several distinct groups (Krabberød et al 2017). One MALV group was associated only with polycystine radiolarians, another group was associated with a mixture of radiolarian and phaeodarian host species, and an additional group was associated only with a single phaeodarian host (Bråte et al 2012, Ikenoue et al 2016.…”
Section: Distance (D Ij )mentioning
confidence: 99%
“…Yet, only 1 study on cultured ciliates (Kolisko et al 2014) and a recent study on natural samples of radiolarian cells (Krabberød et al 2017) have demonstrated that the approach can generate representative data for the total number of expressed genes. Such transcriptome libraries are goldmines for studies of gene function as well as of genes involved in establishing symbiotic relationships.…”
Section: Single-cell Transcriptomicsmentioning
confidence: 99%